2022
DOI: 10.1002/pc.26662
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effect of nano clay addition on microstructures and mechanical properties of epoxy and polyester reinforced glass/sisal hybrid polymer composites

Abstract: In the present study, a comparison has been made between the mechanical properties of polyester and epoxy matrices reinforced Sisal/S‐Glass, and also the effects of nano clay addition have been studied. For fabrication of composites, Glass/Sisal fibers are reinforced with Polyester and Epoxy with various wt% of nano clay. These composites are fabricated through the hand lay‐up technique. Various wt% of nano clay are 2, 4, 6 wt%, and the stacking sequence of fibers are GSSG (S‐Glass/Sisal/Sisal/S‐Glass). The va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…where [Q G/E ] and [Q E ] are given by equations ( 4) and (8). The elements of σ ij are i, j = {1, 2, 6}.…”
Section: Constitutive Model For Epoxymentioning
confidence: 99%
See 1 more Smart Citation
“…where [Q G/E ] and [Q E ] are given by equations ( 4) and (8). The elements of σ ij are i, j = {1, 2, 6}.…”
Section: Constitutive Model For Epoxymentioning
confidence: 99%
“…Energy absorption is to be higher for samples with more GFRP layers in the rear face sheet. Chowdary et al [8] have reported that the static tensile strength of epoxy/Glass/Sisal/Sisal/Glass fibers (GSSG) and polyester/GSSG hybrid composites, each with 4 wt.% of nanoclay, improves by 18 and 16%, respectively. The static flexural strength of former composites with 2 wt.% of clay increases by 16 and 24%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resin (EP) is a widely employed thermosetting polymer material. [9][10][11] Thus, the modification of EP has been addressed extensively, such as adding functional particles to improve the thermal conductivity, 12 electrical conductivity 13 and flame resistance, 14,15 adding CNTs, 16 nano-clays, 17,18 inorganic alumina, 19,20 graphene oxide, [21][22][23] functionalized aramid nanofibers (fANFs), 24,25 pyrolyzed carbon black, 26 and other hybrid fillers 27,28 to enhance its comprehensive mechanical properties. Our previous studies have shown that the aminated PPTA can significantly strengthen and toughen triglycidyl-p-aminophenol (TGPAP) epoxy resin and its carbon fiber composite, and having little effect on the T g of EP.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] Incorporating inorganic particle fillers into polymer matrixes has improved the matrix's tribological and mechanical properties. [ 16 ] It should be noted that there is very little literature on Nano filler addition to hybrid composites. The mechanical characteristics of hybrid composites vary significantly when high surface area fillers are added.…”
Section: Introductionmentioning
confidence: 99%